Zingiber officinale (Ginger) Candy Therapy as an Antiemetic in Primiparous Pregnant Women with Emesis Gravidarum: Experimental Study - Afrida, Baiq Ricca; Aryani, Ni Putu; Idyawati, Susilia; Jannari, Sri Hawari; Jannah, Raudatul (Fakultas Kedokteran, 2024)
Emesis Gravidarum is nausea and vomiting experienced by pregnant women, especially in the first trimester. The prevalence of this condition reaches 73.1% in the first trimester and 47.1% in primigravida. WHO data from 2018 shows that 21.5% of pregnant women in the world experience emesis gravidarum at eight weeks of pregnancy. In Indonesia, the prevalence of nausea and vomiting increased from 5.31% in 2018 to 5.42% in 2019. Proper handling is important to prevent more serious conditions such as hyperemesis gravidarum, which occurs in 31% of pregnant women in NTB Province. Ginger (Zingiber officinale) contains gingerol and shogaol, which relieve nausea and vomiting. This study aims to assess the effectiveness of ginger candy as an antiemetic in primiparous pregnant women in Reriu Hamlet, Bagik Payung Village, East Lombok. This study used a one-group pretest-posttest pre-experimental design with 31 respondents. The results showed a significant decrease in the Rhodes Index of Nausea, Vomiting, and Retching (RINVR) score from 14.8 to 7.6 after two weeks of giving ginger candy. The Paired T-Test showed a significant difference with a p-value = 0.0001. These results indicate that ginger candy is effective in reducing nausea and vomiting in pregnant women, so it can be used as a safe, non-pharmacological alternative.Keywords: emesis gravidarum, ginger candy, antiemetic, pregnant women